PENGARUH MODEL PEMBELAJARAN SAVI (SOMATIC, AUDITORY, VISUAL, INTELLECTUAL) DAN GAYA BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI KELAS VII SEKOLAH MENENGAH PERTAMA MANBAUL ULUM TANGSIL WETAN WONOSARI BON - FAIZIYAH, ROBITOTUL (IJIT: Indonesian Journal of Islamic Teaching, 2019)
Abstract: Student learning processes are influenced by emotions. If students feel compelled to take part in a lesson, students will find it difficult to accept the lessons or materials provided by the teacher. Therefore, the teacher must be able to create a conducive atmosphere and make the lesson effective and enjoyable with give attention to student learning styles. In order for learning to be fun, there needs to be a change in teaching methods from traditional learning models to innovative learning models through SAVI (Somatic, Auditory, Visual, Intellectual) learning . This study aims to determine the differences in the influence of the SAVI learning model and conventional learning models and learning styles on the learning outcomes of class VII students of Manbaul Ulum Tangsil Wetan Middle School Wonosari Bondowoso on Islamic Education and Character, subject matter of thaharah. This type of research is quasi-experimental using Factorial 2x2 3. The study population was all students of class VII of Manbaul Ulum Tangsil Wetan Middle School Wonosari Bondowoso 2018/2019 academic year totaling 173 students. Sampling was done by cluster sampling with a sample of 77 students and classes selected were class VII A (38 students) and VII B (39 students). Methods of collecting data with tests and documentation. Hypothesis testing is done by SPSS 22 program using Two Way ANOVA analysis. The results of data analysis using a 5% significance level were obtained: (1) there were differences in the influence of SAVI and conventional learning models on student learning outcomes, with a significance value of 0.000, (2) there were differences in learning outcomes based on student learning styles consisting of visual learning styles, auditory , which is indicated by a significance value of 0.000 Learning outcomes of students who have visual, auditory, and kinesthetic learning styles in the SAVI learning experiment class as a whole are higher than the learning outcomes of conventional learning models, and (3) there is interaction of SAVI learning models with learning styles towards learning outcomes of PAI and Budi Pekerti on the subject of thaharah, which can be seen from the significance value of 0.045 at the 0.05 significance level.